ANALYZING THE IMPACT OF UNAUTHORIZED IMMIGRATION: A STUDY OF INDIAN POLICIES IN GLOBAL COMPARATIVE CONTEXT (International Journal of Food and Nutritional Sciences, 2025)
Abstract Unauthorized immigration has been a pressing global issue, affecting economies, social structures, and national security. This study examines the impact of unauthorized immigration in India while drawing comparisons with global policies. It explores policy frameworks, socio-economic consequences, security challenges, and potential solutions, emphasizing a balanced approach to regulation and humanitarian considerations.